The Effectiveness of the Online Non-Tax State Revenue Information System (SIMPONI) in the Management of Traffic Fines (A Case Study of the Jambi State Prosecutor's Office) - Irmayasari, Olivia Renny; Hakim, Muhajir R. (Contemporary Society and Politics Journal, 2023)
The SIMPONI application is an integrated and comprehensive web-based online computerized system that can be accessed at any time to generate valid data reports in the management of non-tax state revenue. Traffic fines are one of the non-tax state revenues whose amounts are determined by court decisions based on the Indonesian Law Number 22 Year 2009 concerning Traffic and Road Transportation. The process of managing traffic fines in the Jambi State Prosecutor's Office is still done manually, even though the number of traffic violations in the city of Jambi is relatively high. If the data processing process is not accompanied by technological updates, an ineffective and inefficient work system will be created. The purpose of this study is to examine the effectiveness and efficiency of the integration between SIMPONI and the e-tilang application of the Indonesian State Prosecutor's Office in the Jambi State Prosecutor's Office working area. The results of this study can be known through the e-tilang application of the Indonesian State Prosecutor's Office v.2.0, where the public can directly pay traffic fines to the state treasury using billing codes. This application has been integrated with SIMPONI, making it easier for officers to reconcile non-tax state revenue, which serves as the basis for financial reporting.